1993
DOI: 10.2151/jmsj1965.71.2_195
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Radar Echoes and their Relation to Lightning Discharges of Thunderclouds in the Hokuriku District

Abstract: In the present work, winter thunderclouds and active convective clouds were observed by means of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 9 publications
4
32
0
Order By: Relevance
“…This height is known to be very important in the charge separation (Takahashi, 1978;Rakov and Uman, 2003), which is considered to be the 1st order approximation for the charge height. The location of the -10°C isotherm above the ground level was found to be a decisive factor for lightning activity in winter (Michimoto, 1993), and no lightning is observed in situations when it is at or below 1.4 km. The average (or mean) value is plotted as a square against each month, with the standard deviation shown as a bar.…”
Section: Analysis Results (Monthly Basis)mentioning
confidence: 94%
See 2 more Smart Citations
“…This height is known to be very important in the charge separation (Takahashi, 1978;Rakov and Uman, 2003), which is considered to be the 1st order approximation for the charge height. The location of the -10°C isotherm above the ground level was found to be a decisive factor for lightning activity in winter (Michimoto, 1993), and no lightning is observed in situations when it is at or below 1.4 km. The average (or mean) value is plotted as a square against each month, with the standard deviation shown as a bar.…”
Section: Analysis Results (Monthly Basis)mentioning
confidence: 94%
“…There are two fundamental ones; (1) sprites that develop in the mesosphere (Sentman and Wescott, 1995) and (2) elves which are detected in the lower ionosphere (Fukunishi et al, 1996). It is generally agreed that elves are caused by heating and ionization by the electromagnetic pulse (EMP) from ground flashes (Nickolaenko and Hayakawa, 1995;Inan et al, 1996). Whereas, it is generally suggested that sprites occur due to the quasi-electrostatic (QE) electric field originating from the negative charge left in the thundercloud after the parent positive cloud-to-ground (CG) strokes (Pasko et al, 1995(Pasko et al, , 1997a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] In reference to (3) of the conclusion, a Trimpi is easily triggered around the Sea of Japan where there seems to be a tendency for higher percentage of ground flashes to lower positive charge, and positive ground flashes occasionally lower extremely large amounts of charge [Michimoto, 1993]. These thunderstorms are formed over the Sea of Japan, often in or to the rear of fronts.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[Brook et al, 1982;Takeuti and Nakano, 1983;Michimoto, 1993]. However, in the winter season around Japan, a large number of lightning discharges seem to occur not only in the areas of Sea of Japan, but also Pacific area.…”
Section: Occurrence Rate Of Trimpis In Relation To Lightning Areamentioning
confidence: 99%